“Can You Just Move the Curtain?”: Stories of Women from the Educational Underclass at the College Door - Janet Kaplan-Bucciarelli (Adult Education Research Conference, 2019)
This study explores prospective students’ lives and beliefs about college, and proposes principles and practices that respond holistically to learners’ strengths and vulnerabilities rather than emphasizing academic deficiencies.
Keywords: non-traditional; community college; women; transition